Effect of corroded tension reinforcements on flexural performance of reinforced recycled aggregate concrete beams strengthened with CFRP. (1st April 2019) - Zhang, Huifeng; Wu, Jin; Jin, Fengyu; Zhang, Chengjun
Abstract: This paper reports the effect of corroded tension reinforcements on the flexural behavior of reinforced recycled aggregate concrete (RRC) beams strengthened with carbon fiber-reinforced polymer (CFRP). Eight beams were subjected to accelerated corrosion for 2, 4, 6, 8, 10, 12, and 14 days to obtain the theoretical mass loss in their tension reinforcements of 1%, 3%, 5%, 7%, 9%, 11%, and 13%, respectively. The specimen beams were categorized into two groups (strengthened and unstrengthened). First, strengthened group included SB0–SB7.Seconded, unstrengthened group included B0 and B7. The results indicated that the flexural bearing capacity of the RRC beam decreased with increasing tension reinforcement corrosion level. The flexural bearing capacity of the RRC beams strengthened with CFRP improved more significantly. The CFRP strengthening effect of corroded RRC beams was more obvious than that of corroded RC beams under the same corrosion level. The specimens failed owing to tension reinforcements yielding, the compression concrete was crushed and subsequently the CFRP debonding the concrete. The corroded RRC beams, strengthened by adhering CFRP sheets, could restrict the development and extension of the cracks.